The role of scientific knowledge in Extinction Rebellion's communication of climate futures - Karnik Hinks, Ella; Rödder, Simone (Frontiers in Communication, 2023)
Extinction Rebellion (XR) are one of the central players in climate movements in the United Kingdom. Considering the historical relationship that environmentalists have had with science and scientific knowledge, we examine the current treatment of science in the narrative put forward by XR UK. Using mixed qualitative methods, the group’s online press releases for the year 2019 were analysed, alongside fieldwork from two weeks spent at the United Nations’ climate conference in Glasgow in 2021. The fieldwork data consists of participant observation combined with semi-structured interviews. The findings show positioning of science as a supreme authority, which acts to depoliticise the discourse and acts as a form of reductionism in imagining climate futures. This, combined with the centrality of apocalyptic imagery hampers the construction of alternative futures and fails to engage meaningfully with climate justice.